Manajemen Konflik Dalam Meningkatkan Kedisiplinan Guru (Studi Kebijakan Di Smp Al-Kautsar Tanjungpinang Kepulauan Riau) - Ainur Rofiq (Nidhomul Haq : Jurnal Manajemen Pendidikan Islam, 2018)
The background of this research that conflict is a natural moment and we usually find of our life, especially in the education institution. Conflict can’t be avoided. Conflict in the junior high school of Al-Kautsar involves between headmaster and teachers. It happens because of many policy of headmaster and disciplineless of teachers. There are many method to manage and to solve conflict. This research is to describe conflict and conflict management of headmaster leadership in the junior high school of Al-Kautsar. The kind of this research is field reseach with qualitative research method. The method of data’s analysing uses milles and huberman. The method to find data’s is observation, deepth interview and documentation. Then the technic to crosscheck about validity of data’s is triangulation technic and source, validity, and normality. The source of research data is director, headmaster, vice head and teachers in the junior high school of Al-Kautsar. Technic of analysing data’s for qualitative is reduction display, evaluation and data’s verification. This result of research shows that: First: conflict that happens between headmaster and teachers in the junior high school is caused by many method and ego of headmaster and teachers. Second: the awareness of discipline of the teachers is still low, especially to understand the rule that has been decided. Third: it is very important to increase coordination and socialization between headmaster and teachers to conflict management at Al-Kautsar’s junior high school so that there are much perception and goal in order to increace quality of education. Actually headmaster and teachers are one of success determining in the education institution, especially at school. Conflict can be solved or managed to be a productive thing. It must be managed by manager or leader of education organization and it can be mediated by expert of conflict management.